1989
DOI: 10.1111/j.1476-5381.1989.tb11845.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an intracellular action of platelet‐activating factor in bovine cultured aortic endothelial cells

Abstract: Bovine culture endothelial cells (BAECs) generate platelet-activating factor (Pat) following activation by bradykinin (Bk O.1nM), the ionophore, A23187 (31iM), and ATP (10piM), but Paf is not released from the cells.These stimuli also elicit generation of prostacyclin (PGI2). The specific and competitive Paf receptor antagonists, WEB 2086 (0.1-1.OpM) and CV 6209 (0.01-0.1 pM), inhibited Bk-, A23187-and, to a lesser extent, ATP-induced PGI2 generation but had no effect on basal PGI2 generation. These data sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…However, it is also possible that the low apparent affinities were due to decreased access of the antagonists to a receptor located intracellularly. The possibility of an intracellular site of action is also supported by our recent observation that Paf receptor antagonists inhibit bradykinin-induced prostacyclin (PGI2) generation by cultured endothelial cells (Stewart et al, 1989).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…However, it is also possible that the low apparent affinities were due to decreased access of the antagonists to a receptor located intracellularly. The possibility of an intracellular site of action is also supported by our recent observation that Paf receptor antagonists inhibit bradykinin-induced prostacyclin (PGI2) generation by cultured endothelial cells (Stewart et al, 1989).…”
Section: Introductionsupporting
confidence: 51%
“…These data suggest that intracellular Paf releases AA from its phosphatide stores, leading to eicosanoid generation. We have recently proposed that intracellular Paf has a role in AA mobilization in cultured endothelial cells (Stewart et al, 1989 cluded that the inhibition takes place at the level of the generation of non-esterified AA. The stimuli used in this study have been reported to elicit significant leukotriene formation in other macrophage populations (Rouzer et al, 1982;Rhodes et al, 1985;Williams et al, 1986;Schade et al, 1987;Kouzan et al, 1988 (Rouzer et al, 1982;Kouzan et al, 1988) or radioimmunoassay (Rhodes et al, 1985;Williams et al, 1986) which may provide greater sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that bradykinininduced PAF generation is involved in the response although we have shown previously that PAF-induced plasma leakage is unaffected by pretreatment with indomethacin (Evans et al, 1987). However, endogenous release of PAF may generate prostaglandins because PAF antagonists will block bradykinin-induced PGI2 generation by bovine endothelial cells in vitro (Stewart et al, 1989). Of the prostaglandins possibly generated, thromboxane has not been shown to affect leakage (Chung et al, 1990) and is unlikely to be involved.…”
Section: Discussionmentioning
confidence: 93%
“…Maximal inhibition of the early phase of leakage was approximately 50% and included doses of WEB 2086 which we have shown to block completely equivalent PAF-induced leakage . Similarly, inhibition approached 50% at a dose of BN 52021 shown previously to inhibit markedly PAFinduced bronchoconstriction (Braquet et al, 1985 (McIntyre et al, 1985) and bovine aorta (Stewart et al, 1989). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation